DETERMINANTS OF NON-COMPLIANCE TO IRON AND FOLIC ACID SUPPLEMENTATION AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC IN NAKURU NORTH SUB-COUNTY, KENYA - WAMBUGU, JACINTA NJAMBI (Kabarak University, 2023)
Iron and folic acid are micronutrients that are essential for normal physiological function, growth and development as well as maintenance of life. Iron and folic acid supplementation (IFAS) is one of the most affordable and effective global intervention strategies for control of anaemia in pregnancy with resultant benefits of reduced maternal-child morbidity and mortality. Despite high prevalence of anaemia in Kenya, minimal information on determinants leading to IFAS non-compliance exists hence the need for this study. A mixed methods study targeting pregnant women in Nakuru North Sub County was carried out to establish the determinants of non-compliance. Systematic random sampling was used to obtain the study subjects based on the inclusion criteria targeting 279 respondents. A semi structured questionnaire was used to collect quantitative data while Key Informant Interview and Focus Group Discussion guides were used to collect qualitative data. Data was coded, cleaned, sorted, and entered into the statistical package for social sciences (SPSS), version 21 for analysis. Descriptive statistics were used to summarize the data, and the results presented using charts, graphs and tables. Bivariate analysis was conducted using Chi-square (at a significance level of P = 0.05), to ascertain the significance of association between various demographic and socio-economic characteristics of the women attending ANC. Finally, odds ratio was performed to determine the influence of the various factors on non-compliance of IFA supplements. Inferences were drawn based on the study findings at 95% level of significance. The qualitative data was organized, coded and combined into themes. The study findings revealed that 27.1% of the respondents were non-compliant. Reasons for non-compliance were given as side effects, bad taste and missed clinics. About a third (37.6%) of the participating pregnant women first visited the Antenatal Clinic when they were over four months pregnant and (31.8%) indicated that they had not received information on the benefits of IFAS. The HB levels of most (90.7%) of the participants were normal between 11.0 and 15.0g/dl. Chi square tests showed that there was a significant relationship between IFAS non-compliance status and HB levels (χ2= 59.791, P value= 0.0271) while odds ratio indicated that pregnant women were more likely to comply if they did not have side effects (OR=1.47), initiated ANC early (OR=1.33) and there was a constant supply of IFAS (OR=1.24). Therefore, this study demonstrated that the mother related determinants of non- compliance were lack of knowledge about the benefits of IFAS, side effects and late ANC attendance while the facility related determinant was IFAS stock outs. Thus, the study recommends a review of the advice given to pregnant mothers visiting ANC to improve IFAS compliance and capacity building of health workers on proper forecasting to avoid stock outs.
Keywords: Iron and Folic acid; Non-compliance; Maternal factors; Health facility factors